Strategies of Moral Faith Teachers in Integrating SDGs-Based Character Education in Islamic Boarding Schools - Inda Amelia; Dewi Hasanah; Maisuna Mustapha Yahya (Profetika: Jurnal Studi Islam, 2026)
Objective: This study analyzes the pedagogical strategies of Akidah Akhlak teachers in integrating SDGs-based character education at Al-Jauharen Islamic Boarding School, Jambi City, focusing on discipline, honesty, and responsibility. Theoretical framework: The research is grounded in character education theory, value internalization, and contextual pedagogy, aligned with SDGs principles that emphasize inclusive, equitable, and value-oriented education. Literature review: Previous studies indicate that Akidah Akhlak learning remains largely cognitive and memorization-oriented, limiting effective character internalization, while empirical studies on teacher strategies in pesantren contexts and their linkage to SDGs are still limited. Method: This study employs a qualitative descriptive-analytical approach involving teachers, school leaders, and students, using interviews, observations, and documentation, analyzed through the Miles and Huberman model with triangulation. Results: Findings reveal that SDGs-oriented character integration is implemented through structured planning, teacher exemplification, value habituation, and reflective discussions rooted in students’ experiences and strengthened by pesantren culture; however, it remains insufficiently systematic, particularly in evaluation, and is constrained by time and students’ psychological factors. Implications: The study highlights the need for more reflective, contextual, and sustainable pedagogical strategies aligned with SDGs, ensuring that character values are internalized beyond normative understanding into real student behavior. Novelty: This research offers an empirical contribution by specifically examining SDGs-based character education integration strategies in Akidah Akhlak learning within a pesantren-based madrasah context, which remains underexplored.